2021
DOI: 10.3389/fmicb.2021.743126
|View full text |Cite
|
Sign up to set email alerts
|

Unique Features of Mycobacterium abscessus Biofilms Formed in Synthetic Cystic Fibrosis Medium

Abstract: Characterizing Mycobacterium abscessus complex (MABSC) biofilms under host-relevant conditions is essential to the design of informed therapeutic strategies targeted to this persistent, drug-tolerant, population of extracellular bacilli. Using synthetic cystic fibrosis medium (SCFM) which we previously reported to closely mimic the conditions encountered by MABSC in actual cystic fibrosis (CF) sputum and a new model of biofilm formation, we show that MABSC biofilms formed under these conditions are substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 62 publications
0
60
0
Order By: Relevance
“…To determine whether 2-AI-based small-molecule compounds and related scaffolds inhibited the formation of M. abscessus biofilms, we screened a library of 30 compounds, including twenty-six 2-AI analogs, one 2-AP compound (EL-05-047) and three meridianin analogs (7.079; 7.025 and 8.001), of which two contained the 2-AI moiety ( Table 1 ). The screening was conducted using the Mmas reference strain CIP 108297 grown as submerged biofilms on poly-D-lysine-coated plates in chemically defined synthetic CF medium (SCFM) as previously described [ 11 ]. Recent studies from our laboratory have indeed shown that SCFM closely mimics the nutritional conditions encountered and metabolic adaptation undergone by M. abscessus grown in actual CF sputum [ 26 ], making this model more relevant to infection than other models based on laboratory media.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine whether 2-AI-based small-molecule compounds and related scaffolds inhibited the formation of M. abscessus biofilms, we screened a library of 30 compounds, including twenty-six 2-AI analogs, one 2-AP compound (EL-05-047) and three meridianin analogs (7.079; 7.025 and 8.001), of which two contained the 2-AI moiety ( Table 1 ). The screening was conducted using the Mmas reference strain CIP 108297 grown as submerged biofilms on poly-D-lysine-coated plates in chemically defined synthetic CF medium (SCFM) as previously described [ 11 ]. Recent studies from our laboratory have indeed shown that SCFM closely mimics the nutritional conditions encountered and metabolic adaptation undergone by M. abscessus grown in actual CF sputum [ 26 ], making this model more relevant to infection than other models based on laboratory media.…”
Section: Resultsmentioning
confidence: 99%
“…Since Zn 2+ ions are naturally absent from SCFM, where M. abscessus forms abundant biofilms, one can exclude that AB-2-29 prevents biofilm formation by acting as a zinc chelator. Likewise, we exclude that the amount of zinc that comes with AB-2-29 (2.52 μM of zinc at its IC 50 value of 20 μM) is responsible for the observed antibiofilm activity of this compound, since we previously established that much higher concentrations of zinc were required to inhibit M. abscessus biofilm formation in SCFM (IC 50 of zinc~150 μM against Mabs NJH12) [ 11 ]. The fact that AB-2-29 comes with small quantities of zinc, however, explains the repression of zur regulon genes in AB-2-29-treated cultures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations